2021
DOI: 10.1037/cep0000238
|View full text |Cite
|
Sign up to set email alerts
|

« Moi d’abord ! » ou l’égocentrisme ordinaire : Une revue critique de l’effet de priorité au Soi.

Abstract: The self is a crucial component of the psychic life and plays a central role for the adaptation to the environment. In daily life, this adaptative function is ensured, inter alia, by numerous biases filtering information and favoring those which are self-related. After succinctly reviewing the most documented among them which are affective and mnesic biases, the current paper provides a critical review of literature about a bias which is supposed to be perceptive, the self-prioritization effect (SPE). That has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 169 publications
(412 reference statements)
0
1
0
Order By: Relevance
“…There is a debate regarding whether familiarity or self-relevance underpins the perceptual prioritisation of self-related stimuli (Maire, 2021). Previous research has demonstrated that familiar voices receive special treatment at a cognitive and neurological level (Kanber et al, 2022;Plante-Hébert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a debate regarding whether familiarity or self-relevance underpins the perceptual prioritisation of self-related stimuli (Maire, 2021). Previous research has demonstrated that familiar voices receive special treatment at a cognitive and neurological level (Kanber et al, 2022;Plante-Hébert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%